PENGARUH KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN DENGAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Najah, Hikmah Wati; Atiningsih, Suci (Universitas Muhammadiyah Palembang, 2023)
This research aims to empirically prove the effect of dividend policy on company value and audit quality moderating dividend policy on company value in manufacturing companies listed on the Indonesia Stock Exchange for the period 2019 - 2021. The population is 195 companies. Of the 195 companies, only 110 companies met the research criteria. Research period 2019 – 2021 with observation data from 330 companies. The final sample was 174 with details of 58 companies with 3 years of observations after data outliers. Sampling used purposive sampling technique. This research is quantitative research using the linear regression method through the IBM SPSS 22 application. The results of this research are that dividend policy has a positive effect on company value. Audit quality has a positive effect on company value. Audit quality as a moderating variable strengthens the influence of dividend policy on company value.